(untitled) (The Review of Diabetic Studies, 2025)
Mother’s milk contains high nutrition which is very beneficial for baby’s health. WHO recommends that babies should get exclusive breastfeeding for 6 months. But unfortunately for work reasons, not all women can give exclusive breastfeeding to their babies. The aim of the current study was to conduct a global systematic literature review exploring how breastfeeding patterns of mothers work towards achieving exclusive breastfeeding. This study used a systematic review of research articles published on breastfeeding in the online article databases PubMed, Proquest, Scopus, Sciencedirect and Google Schoolar. This systematic review followed the guidance of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). This study shows that of the 12 selected articles there are several contributing factors, namely: Knowledge, Attitudes, Nutrition, Emotional, Lactation Consultation, Family support (husband, parents, in-laws), Self-confidence, Lactation management in working mothers, Economy, Frequency of Breastfeeding, Length of hours worked, Availability of lactation facilities, Caregiver support, Length of Maternity Leave and No nursing leave system. This review highlighting the provision of exclusive breastfeeding to babies by working mothers, where there are still many mothers who cannot provide exclusive breastfeeding to their babies on the grounds that they are working. We recommends that working mothers are given leeway at work so that they can breastfeed their babies without any additional food until the baby is 6 months old, with the final result, the percentage of exclusive breastfeeding continues to increase. Finally, this review getsused as useful evidence when making policies regarding exclusive breastfeeding by working mothers.